ANALISIS KINERJA KANTOR PELAYANAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI (Studi Empiris Pada Wajib Pajak Orang Pribadi di KPP Pratama Pekanbaru Senapelan) - Christin Junianty; Kamaliah -; Rofika - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to examine the effect of Productivity, Responsibility, Accountability, and Education. The population in this study were all individuals who belong to individual taxpayers registered in the tax office Senapelan. Types of samples used by researchers convinience. The sample in this study is an individual taxpayer who never enjoyed the service at the Tax Office Primary Senapelan Pekanbaru. The sample used in this study was 100 respondents. The hypothesis is then tested using multiple linear regression analysis with SPSS version 17.0. These results indicate that productivity and education effect on tax compliance. While responsibility and accountability no significant impact on taxpayer compliance. The magnitude of the effect of the independent variable on the dependent variable was 36.5%. While the remaining 63.5% is influenced by other variables not included in this regression model.Keywords: productivity, responsibility, accountability, and education.